Impact of Membrane Lipids on UapA and AzgA Transporter Subcellular Localization and Activity in Aspergillus nidulans - Mariangela Dionysopoulou; George Diallinas (Journal of Fungi, 2021)
Recent biochemical and biophysical evidence have established that membrane lipids, namely phospholipids, sphingolipids and sterols, are critical for the function of eukaryotic plasma membrane transporters. Here, we study the effect of selected membrane lipid biosynthesis mutations and of the ergosterol-related antifungal itraconazole on the subcellular localization, stability and transport kinetics of two well-studied purine transporters, UapA and AzgA, in Aspergillus nidulans. We show that genetic reduction in biosynthesis of ergosterol, sphingolipids or phosphoinositides arrest A. nidulans growth after germling formation, but solely blocks in early steps of ergosterol (Erg11) or sphingolipid (BasA) synthesis have a negative effect on plasma membrane (PM) localization and stability of transporters before growth arrest. Surprisingly, the fraction of UapA or AzgA that reaches the PM in lipid biosynthesis mutants is shown to conserve normal apparent transport kinetics. We further show that turnover of UapA, which is the transporter mostly sensitive to membrane lipid content modification, occurs during its trafficking and by enhanced endocytosis, and is partly dependent on autophagy and Hect-type HulARsp5 ubiquitination. Our results point out that the role of specific membrane lipids on transporter biogenesis and function in vivo is complex, combinatorial and transporter-dependent.